Analyzing the transmission of visible light through electrospun nanofibrous PCL scaffolds - Himmler, Marcus; Garreis, Fabian; Paulsen, Friedrich; Schubert, Dirk W.; Fuchsluger, Thomas (Nordic Polymer Days, Helsinki (Finland), 2021, 2021)

Biomaterialien als DMEK-& Amnionmembranersatz - Himmler, Marcus; Schubert, Dirk W.; Fuchsluger, Thomas (2. Baltic Sea Eye Conference, Rostock (Deutschland), 2020, 2020)

Cultivation and characterisation of primary retinal pigment epithelium cells on nanofibre scaffolds - Heiduschka, Peter; Zimmermann, Julian Alexander; Plagemann, Tanja; Stafiej, Piotr; Himmler, Marcus; Fuchsluger, Thomas Armin; Eter, Nicole (INVESTIGATIVE OPHTHALMOLOGY & VISUAL SCIENCE, 2019)
CRIS-Team WoS Importer:2019-10-29

Electrical and mechanical characterization of medical grade silicones as dielectric layers in aerosol jet printed dielectric elastomers - Martin, Sina; Himmler, Marcus; Bruns, Arne; Reitelshöfer, Sebastian; Pham, Duc Huy Hoang; Schubert, Dirk W.; Franke, Jörg (Proceedings Volume 11587, Electroactive Polymer Actuators and Devices (EAPAD) XXIII, 2021)
The name artificial muscles has given dielectric elastomer actuators much attention in the field of medical technology. In healthcare applications, these compliant materials are particularly suitable for soft and lightweight actuators and in addition, they show many advantageous properties such as great extensibility for on-body sensors. However, the lack of industrial scaled production capabilities is still a limiting factor in the transfer of these promising materials into a broad application. To address this issue, we have modified an aerosol jet printer for automated stacking of electrodes and dielectric layers in one process device, which is described in earlier publications. As the performance is mainly dependent on the electrical and mechanical characteristics of the dielectric, a broad material variety is required to face different tasks in healthcare technology. Therefore, different medical grade silicones are investigated in this paper regarding the suitability for aerosol jet printing. In a first step, the printing parameters are derived from rheological testing of the uncured components that are used pure and in mixture with silicone oils to vary the specific Young’s module. Through heat application and dilution, the range for printable materials increases to silicones with initial viscosities up to 8200 mPas. Subsequently aerosol jet printing is used to manufacture stacked silicone dielectrics that are then investigated regarding their mechanical and electrical characteristics for dielectric elastomers. Finally, the collected parameters are compared and an overview of the feasible property combinations is given which can be used as a material guideline for different applications.<br
Keywords: dielectric elastomers; medical grade silicones; mechanical characterization; electrical testing; additive manufacturing; rheological measurement; aerosol jet printing

Electrospun nanofiber membranes as substitutes for posterior lamellar keratoplasty - Himmler, Marcus; Garreis, Fabian; Paulsen, Friedrich; Schubert, Dirk W.; Fuchsluger, Thomas A. (16th Biennial - Bayreuther Polymer Symposium, 2019)

Electrospun nanofiber membranes as substitutes for posterior lamellar keratoplasty - Himmler, Marcus; Garreis, Fabian; Paulsen, Friedrich; Schubert, Dirk W.; Fuchsluger, Thomas (30th Annual Conference of the European Society for Biomaterials, Dresden (Deutschland), 2019, 2019)

Electrospun nanofiber membranes as substitutes for posterior lamellar keratoplasty - Himmler, Marcus; Garreis, Fabian; Paulsen, Friedrich; Schubert, Dirk W.; Fuchsluger, Thomas (16th Bayreuther Polymer Symposium, Bayreuth (Deutschland), 2019., 2019)

Electrospun PCL-Collagen nanofiber membranes as substitute for posterior lamellar keratoplasty - Himmler, Marcus (6th International Symposium on Interface Biology of Implants, 2019)

Electrospun PCL-Collagen nanofiber membranes as substitute for posterior lamellar keratoplasty - Himmler, Marcus; Garreis, Fabian; Paulsen, Friedrich; Schubert, Dirk W.; Fuchsluger, Thomas (Nordic Polymer Days, Trondheim (Norwegen), 2019)

Electrospun PCL-Collagen nanofiber membranes as substitute for posterior lamellar keratoplasty - Himmler, Marcus; Garreis, Fabian; Paulsen, Friedrich; Schubert, Dirk W.; Fuchsluger, Thomas (The Association for Research in Vision and Ophthalmology (ARVO), 2019)

Electrospun PCL Scaffolds as Drug Carrier for Corneal Wound Dressing Using Layer-by-Layer Coating of Hyaluronic Acid and Heparin - Himmler, Marcus; Schubert, Dirk W.; Daehne, Lars; Egri, Gabriella; Fuchsluger, Thomas A. (International Journal of Molecular Sciences, 2022)
Due to its ability to reduce scarring and inflammation, human amniotic membrane is a widely used graft for wound dressings after corneal surgery. To overcome donor dependency and biological variances in the donor tissue, artificial nanofibrous grafts acting as drug carrier systems are promising substitutes. Electrospun nanofibrous scaffolds seem to be an appropriate approach as they offer the properties of permeable scaffolds with a high specific surface, the latter one depending on the fiber diameter. Electrospun scaffolds with fiber diameter of 35 nm, 113 nm, 167 nm and 549 nm were manufactured and coated by the layer-by-layer (LbL) technology with either hyaluronic acid or heparin for enhanced regeneration of corneal tissue after surgery. Studies on drug loading capacity and release kinetics defined a lower limit for nanofibrous scaffolds for effective drug loading. Additionally, scaffold characteristics and resulting mechanical properties from the application-oriented characterization of suture pullout from suture retention tests were examined. Finally, scaffolds consisting of nanofibers with a mean fiber diameter of 113 nm were identified as the best-performing scaffolds, concerning drug loading efficiency and resistance against suture pullout.
CRIS-Team Scopus Importer:2022-03-25
Keywords: Cornea; Drug delivery; Electrospinning; Heparin; Hyaluronic acid; Layer-by-layer coating; Polycaprolactone; Suture retention test; Wound dressing

Examining the transmission of visible light through electrospun nanofibrous pcl scaffolds for corneal tissue engineering - Himmler, Marcus; Schubert, Dirk W.; Fuchsluger, Thomas A. (Nanomaterials, 2021)
Keywords: Transparency; Cornea; Nanofibers; Electrospinning; Tissue engineering; Polycaprolactone

Hierarchical Slice Patterns Inhibit Crack Propagation in Brittle Sheets - Zaiser, Michael; Hosseini, Seyyed Ahmad; Moretti, Paolo; Mäkinen, Tero; Koivisto, Juha; Poornajar, Mahshid; Himmler, Marcus; Redel, Michael; Schubert, Dirk W.; Alava, Mikko (Physical Review Applied, 2022)
By introducing hierarchical patterns of load-parallel cuts into axially loaded brittle sheets, the resistance to propagation of mode-I cracks is very significantly enhanced. We demonstrate this effect by simulation of two-dimensional beam network models and experimentally by testing paper and polystyrene (PS) sheets that are sliced with a laser cutter to induce load-perpendicular hierarchical cut patterns. Samples endowed with nonhierarchical reference patterns of the same cut density and nonsliced sheets are considered for comparison. We demonstrate that hierarchical slicing can increase failure load, apparent fracture toughness, and work of fracture of notched paper and PS sheets by factors between 2 and 10.<br

Identifying Design Principles for the Transmission of Visible Light through Electrospun Nanofibrous PCL Scaffolds for Corneal Tissue Engineering - Himmler, Marcus; Schubert, Dirk W.; Fuchsluger, Thomas (4. Baltic Sea Eye Conference, Rostock (Deutschland), 2022, 2022)

Identifying key parameters for the transmission of visible light through electrospun nanofibrous PCL scaffolds for ophthalmic applications - Himmler, Marcus; Schubert, Dirk W.; Fuchsluger, Thomas (31th Annual Conference of the European Society for Biomaterials, Porto (Portugal), 2021, 2021)

JoVE Video Dataset - Polykandriotis, Elias; Himmler, Marcus; Mansouri, Shirin; Ruppe, Florian; Grüner, Jasmin; Bräuer, Lars; Schubert, Dirk W.; Horch, Raymund E. (2022)
With the evolution of suture materials, there has been a change in paradigms in primary and secondary tendon repair. Improved mechanical properties allow more aggressive rehabilitation and earlier recovery. However, for the repair to hold against higher mechanical demands, more advanced suturing and knotting techniques must be assessed in combination with those materials. In this protocol, the use of polytetrafluoroethylene (PTFE) as a suture material in combination with different repair techniques was investigated. In the first part of the protocol, both linear tension strength and elongation of knotted against not-knotted strands of three different materials used in flexor tendon repair were evaluated. The three different materials are polypropylene (PPL), ultra-high molecular weight polyethylene with a braided jacket of polyester (UHMWPE), and polytetrafluoroethylene (PTFE). In the next part (ex vivo experiments with cadaveric flexor tendons), the behavior of PTFE using different suture techniques was assessed and compared with PPL and UHMWPE. This experiment is comprised of four steps: harvesting of the flexor tendons from fresh cadaveric hands, transection of the tendons in a standardized manner, tendon repair by four different techniques, mounting, and measurement of the tendon repairs on a standard linear dynamometer. The UHMWPE and PTFE showed comparable mechanical properties and were significantly superior to PPL in terms of linear traction strength. Repairs with four- and six-strand techniques proved stronger than two-strand techniques. Handling and knotting of PTFE are a challenge due to very low surface friction but fastening of the four- or six-strand repair is comparatively easy to achieve. Surgeons routinely use PTFE suture material in cardiovascular surgery and breast surgery. The PTFE strands are suitable for use in tendon surgery, providing a robust tendon repair so that early active motion regimens for rehabilitation can be applie
Keywords: Polytetrafluoroethylene; PTFE; Suture Material; Tendon Surgery; Mechanical Properties; Flexor Tendon Repair; Linear Tension Strength; Cadaveric Upper Limb; Incision; A1 Pulley; Flexor Digitorum Profundus; Tendon Retractor; Traction

Long-term cultivation of retinal pigment epithelium cells on nanofiber scaffolds - Zimmermann, Julian A.; Irlenbusch, Lucy; Hansen, Uwe; Himmler, Marcus; Zeng, Chun; Eter, Nicole; Fuchsluger, Thomas; Heiduschka, Peter (Graefes Archive For Clinical and Experimental Ophthalmology, 2025)
What is known : Key Messages : Retinal pigment epithelium (RPE) cells play an important role in the pathogenesis of degenerative retinal diseases. One therapeutic approach is to transplant healthy RPE cells into the subretinal space. Various nanofiber scaffolds have been used in the past to replace Bruch's membrane. What is new : RPE cells can be stably cultured on polycaprolactone (PCL) and collagen nanofiber scaffolds for up to one year. RPE cells show characteristic properties in terms of cell number, morphology and secretion behaviour on PCL/collagen nanofiber scaffolds.
CRIS-Team Scopus Importer:2025-02-17
Keywords: Cell culture; Cell replacement; Macular degeneration; Nanofiber scaffolds; Porcine retinal pigment epithelium

Molecular structure influence on bending behavior of polyester filaments examined using a modified cantilever bending test - Höhnemann, Tim; Himmler, Marcus; Schubert, Dirk W. (Journal of Applied Polymer Science, 2019)
An experimental setup used to measure the bending stiffness of polymer filaments based on existing cantilever approaches is presented. Additionally, it is utilized to evaluate the influence of molar mass and long‐chain branching on filaments of poly(butylene terephthalate), modified with a multifunctional chain extender. Using shear rheological analysis process limits for extrusion of the modified material were revealed, indicated by a change of the curve shape of van Gurp–Palmen plots. For the processable modified materials, it was found that increasing molar mass and degree of long‐chain branching, caused by the modification, raise the bending stiffness of filaments. Also the Young's modulus was found to increase with the amount of chain extender used, while no difference could be generated by using different linear molar grades of the polymer
Keywords: bending; crosslinking; fibers; mechanical properties; polyesters; polymer bristles; properties and characterization; rheology; spectroscopy; structure‐property relations

Myogenic differentiation of human myoblasts and Mesenchymal stromal cells under GDF11 on NPoly-ɛ-caprolactone-collagen I-Polyethylene-nanofibers - Cai, Aijia; Schneider, Paul; Zheng, Zengming; Beier, Justus P.; Himmler, Marcus; Schubert, Dirk W.; Weisbach, Volker Günter; Horch, Raymund E.; Arkudas, Andreas (BMC Molecular and Cell Biology, 2023)
BACKGROUND: For the purpose of skeletal muscle engineering, primary myoblasts (Mb) and adipogenic mesenchymal stem cells (ADSC) can be co-cultured and myogenically differentiated. Electrospun composite nanofiber scaffolds represent suitable matrices for tissue engineering of skeletal muscle, combining both biocompatibility and stability Although growth differentiation factor 11 (GDF11) has been proposed as a rejuvenating circulating factor, restoring skeletal muscle function in aging mice, some studies have also described a harming effect of GDF11. Therefore, the aim of the study was to analyze the effect of GDF11 on co-cultures of Mb and ADSC on poly-ε-caprolactone (PCL)-collagen I-polyethylene oxide (PEO)-nanofibers. RESULTS: Human Mb were co-cultured with ADSC two-dimensionally (2D) as monolayers or three-dimensionally (3D) on aligned PCL-collagen I-PEO-nanofibers. Differentiation media were either serum-free with or without GDF11, or serum containing as in a conventional differentiation medium. Cell viability was higher after conventional myogenic differentiation compared to serum-free and serum-free + GDF11 differentiation as was creatine kinase activity. Immunofluorescence staining showed myosine heavy chain expression in all groups after 28 days of differentiation without any clear evidence of more or less pronounced expression in either group. Gene expression of myosine heavy chain (MYH2) increased after serum-free + GDF11 stimulation compared to serum-free stimulation alone. CONCLUSIONS: This is the first study analyzing the effect of GDF11 on myogenic differentiation of Mb and ADSC co-cultures under serum-free conditions. The results of this study show that PCL-collagen I-PEO-nanofibers represent a suitable matrix for 3D myogenic differentiation of Mb and ADSC. In this context, GDF11 seems to promote myogenic differentiation of Mb and ADSC co-cultures compared to serum-free differentiation without any evidence of a harming effect.
CRIS-Team Scopus Importer:2023-05-26
Keywords: ADSC; Collagen; Electrospun composite nanofibers; GDF11; Myoblasts; Myogenic differentiation; Myostatin; Nanoscaffolds; poly-ε-caprolacton (PCL); Polyethylene oxide (PEO)

Nanofaserscaffolds als DMEK-& Amnionmembranersatz – Anforderungen und Eigenschaften - Himmler, Marcus; Schubert, Dirk W.; Fuchsluger, Thomas (iSearch 2021, Münster (Deutschland), 2021, 2021)

Optimization of polycaprolactone‑ based nanofiber matrices for the cultivation of corneal endothelial cells - Himmler, Marcus; Garreis, Fabian; Paulsen, Friedrich; Schubert, Dirk W.; Fuchsluger, Thomas A. (Nature Medicine, 2021)
Posterior lamellar transplantation of the eye’ s cornea (DSAEK, DMEK) currently is the gold standard for treating patients with corneal endothelial cell and back surface pathologies resulting in functional impairment. An artificial biomimetic graft carrying human corneal endothelium could minimize the dependency on human donor corneas giving access to this vision‑restoring surgery to large numbers of patients, thus reducing current long waiting lists. In this study, four groups of electrospun nanofibrous scaffolds were compared: polycaprolactone (PCL), PCL/collagen, PCL/gelatin and PCL/chitosan. Each of the scaffolds were tissue‑engineered with human corneal endothelial cells (HCEC‑B4G12) and analyzed with regard to their potential application as artificial posterior lamellar grafts. Staining with ZO‑1 and Na+/K+‑ATPase antibodies revealed intact cell functionalities. It could be shown, that blending leads to decreasing contact angle, whereby a heterogeneous blend morphology could be revealed. Scaffold cytocompatibility could be confirmed for all groups via live/dead staining, whereby a significant higher cell viability could be observed for the collagen and gelatine blended matrices with 97 ± 3% and 98 ± 2% living cells respectively. TEM images show the superficial anchoring of the HCECs onto the scaffolds. This work emphasizes the benefit of blended PCL nanofibrous scaffolds for corneal endothelial keratoplast

Optimization of polycaprolactone - based nanofiber matrices for the cultivation of corneal endothelial cells - Himmler, Marcus; Garreis, Fabian; Paulsen, Friedrich; Schubert, Dirk W.; Fuchsluger, Thomas A. (Scientific Reports, 2021)

Polytetrafluoroethylene (PTFE) as a Suture Material in Tendon Surgery - Polykandriotis, Elias; Himmler, Marcus; Mansouri, Shirin; Ruppe, Florian; Grüner, Jasmin; Bräuer, Lars; Schubert, Dirk W.; Horch, Raymund E. (Journal of Visualized Experiments, 2022)
With the evolution of suture materials, there has been a change in paradigms in primary and secondary tendon repair. Improved mechanical properties allow more aggressive rehabilitation and earlier recovery. However, for the repair to hold against higher mechanical demands, more advanced suturing and knotting techniques must be assessed in combination with those materials. In this protocol, the use of polytetrafluoroethylene (PTFE) as a suture material in combination with different repair techniques was investigated. In the first part of the protocol, both linear tension strength and elongation of knotted against not-knotted strands of three different materials used in flexor tendon repair were evaluated. The three different materials are polypropylene (PPL), ultra-high molecular weight polyethylene with a braided jacket of polyester (UHMWPE), and polytetrafluoroethylene (PTFE). In the next part (ex vivo experiments with cadaveric flexor tendons), the behavior of PTFE using different suture techniques was assessed and compared with PPL and UHMWPE. This experiment is comprised of four steps: harvesting of the flexor tendons from fresh cadaveric hands, transection of the tendons in a standardized manner, tendon repair by four different techniques, mounting, and measurement of the tendon repairs on a standard linear dynamometer. The UHMWPE and PTFE showed comparable mechanical properties and were significantly superior to PPL in terms of linear traction strength. Repairs with four- and six-strand techniques proved stronger than two-strand techniques. Handling and knotting of PTFE are a challenge due to very low surface friction but fastening of the four- or six-strand repair is comparatively easy to achieve. Surgeons routinely use PTFE suture material in cardiovascular surgery and breast surgery. The PTFE strands are suitable for use in tendon surgery, providing a robust tendon repair so that early active motion regimens for rehabilitation can be applied.
CRIS-Team Scopus Importer:2022-11-18

Schwann Cells Promote Myogenic Differentiation of Myoblasts and Adipogenic Mesenchymal Stromal Cells on Poly-ɛ-Caprolactone-Collagen I-Nanofibers - Cai, Aijia; Zheng, Zengming; Himmler, Marcus; Schubert, Dirk W.; Fuchsluger, Thomas A.; Weisbach, Volker Günter; Horch, Raymund E.; Arkudas, Andreas (Cells, 2022)
For the purpose of skeletal muscle tissue engineering, different cell types have been investigated regarding their myogenic differentiation potential, including co-cultured myoblasts and adipogenic mesenchymal stromal cells (Mb/ADSC). As neural cells enhance synaptic junction formation, the aim of this study was to co-culture Schwann cells (SCs) with Mb/ADSC on biocompatible electrospun aligned poly-ε-polycaprolacton (PCL)-collagen I-nanofibers. It was hypothesized that SCs, as part of the peripheral nervous system, promote the myogenic differentiation of Mb/ADSC co-cultures. Mb/ADSC were compared to Mb/ADSC/SC regarding their capacity for myogenic differentiation via immunofluorescent staining and gene expression of myogenic markers. Mb/ADSC/SC showed more myotubes after 28 days of differentiation (p ≤ 0.05). After 28 days of differentiation on electrospun aligned PCL-collagen I-nanofibers, gene expression of myosin heavy chains (MYH2) and myogenin (MYOG) was upregulated in Mb/ADSC/SC compared to Mb/ADSC (p ≤ 0.01 and p ≤ 0.05, respectively). Immunofluorescent staining for MHC showed highly aligned multinucleated cells as possible myotube formation in Mb/ADSC/SC. In conclusion, SCs promote myogenic differentiation of Mb/ADSC. The co-culture of primary Mb/ADSC/SC on PCL-collagen I-nanofibers serves as a physiological model for skeletal muscle tissue engineering, applicable to future clinical application
Keywords: ADSC; myoblasts; myogenic differentiation; mesenchymal stem cells; nanofibers; Schwann cells

Sobetirome rescues α-synuclein-mediated demyelination in an in vitro model of multiple system atrophy - Meszaros, Lisa; Himmler, Marcus; Schneider, Yanni; Arnold, Philipp; Dörje, Frank; Schubert, Dirk W.; Winkler, Jürgen (European Journal of Neuroscience, 2023)
Multiple system atrophy (MSA) is a rare and rapidly progressive atypical parkinsonian disorder characterized by oligodendroglial cytoplasmic inclusions containing α-synuclein (α-syn), demyelination, inflammation and neuronal loss. To date, no disease-modifying therapy is available. Targeting α-syn-driven oligodendroglial dysfunction and demyelination presents a potential therapeutic approach for restricting axonal dysfunction, neuronal loss and disease progression. The present study investigated the promyelinogenic potential of sobetirome, a blood–brain barrier permeable and central nervous system selective thyromimetic in the context of an in vitro MSA model. Oligodendrocyte precursor cells (OPCs) were obtained from transgenic mice overexpressing human α-syn specifically in oligodendrocytes (MBP29 mouse line), a well-described MSA model, and non-transgenic littermates. mRNA and protein expression analyses revealed a substantial rescue effect of sobetirome on myelin-specific proteins in control and α-syn overexpressing oligodendrocytes. Furthermore, myelination analysis using nanofibres confirmed that sobetirome increases both the length and number of myelinated segments per oligodendrocyte in primary murine α-syn overexpressing oligodendrocytes and their respective control. These results suggest that sobetirome may be a promising thyromimetic compound targeting an important neuropathological hallmark of MSA.
CRIS-Team Scopus Importer:2023-12-22
Keywords: MSA; myelin; oligodendrocytes; sobetirome; thyromimetics; α-synuclein

Vascularization of Poly-ε-Caprolactone-Collagen I-Nanofibers with or without Sacrificial Fibers in the Neurotized Arteriovenous Loop Model - Kratzer, Simon; Arkudas, Andreas; Himmler, Marcus; Schubert, Dirk W.; Schneidereit, Dominik; Bauer, Julian; Friedrich, Oliver; Horch, Raymund E.; Cai, Aijia (Cells, 2022)
Electrospun nanofibers represent an ideal matrix for the purpose of skeletal muscle tissue engineering due to their highly aligned structure in the nanoscale, mimicking the extracellular matrix of skeletal muscle. However, they often consist of high-density packed fibers, which might impair vascularization. The integration of polyethylene oxide (PEO) sacrificial fibers, which dissolve in water, enables the creation of less dense structures. This study examines potential benefits of poly-ε-caprolactone-collagen I-PEO-nanoscaffolds (PCP) in terms of neovascularization and distribution of newly formed vessels compared to poly-ε-caprolactone -collagen I-nanoscaffolds (PC) in a modified arteriovenous loop model in the rat. For this purpose, the superficial inferior epigastric artery and vein as well as a motor nerve branch were integrated into a multilayer three-dimensional nanofiber scaffold construct, which was enclosed by an isolation chamber. Numbers and spatial distribution of sprouting vessels as well as macrophages were analyzed via immunohistochemistry after two and four weeks of implantation. After four weeks, aligned PC showed a higher number of newly formed vessels, regardless of the compartments formed in PCP by the removal of sacrificial fibers. Both groups showed cell influx and no difference in macrophage invasion. In this study, a model of combined axial vascularization and neurotization of a PCL-collagen I-nanofiber construct could be established for the first time. These results provide a foundation for the in vivo implantation of cells, taking a major step towards the generation of functional skeletal muscle tissue.<br
Keywords: vascularization of nanofiber scaffolds; neurotization; neoangiogenesis; EPI loop model; AV loop model; PCL-collagen I-nanofiber scaffolds; polyethylene oxide